Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Seni Tari Dengan Menggunakan Metode Discovery Di SMP Negeri 3 Padang - Refina Adeka Putri; Fuji Astuti (SENDRATASIK UNP, 2021)
This research aims to explain and describe the improvement of students' learning outcomes by using Discovery Method in dance learning at SMP Negeri 3 Padang. This research belongs to Class Action Research (PTK). This research was conducted in 2 cycles. Cycle I was conducted in three meetings and cycle II was conducted in two meetings. The instruments used in this study were knowledge tests (cognitive) and skill tests (psychomotors). The data used were primary and secondary data.  The data were collected through literature study, observation, learning outcome tests (performance test), and documentation. The data analysis was done by using percentage formula. The results show that the use of discovery method in Culture and Arts learning, especially dance learning in grade VIII.3 of SMP Negeri 3 Padang, can improve students’ learning outcomes, and the students are directly involved in learning, especially dance practice learning. With the support of media, the students’ disinterest in the learning process can be avoided. It can also foster student creativity, and learning is more enjoyable because of the existence of media used by teachers. This is proven by the study results of grade VIII.3 students in cycle I. The overall students’ learning results of psychomotor and cognitive test are 57.74. In cycle II, the overall students’ learning results of psychomotor and cognitf are 87.58. Thus, there has been an increase in the results of dance learning using discovery method, and the targets have been successfully achieved.